Anti-Inflammatory and Antimicrobial Effects of Flavonoids from Heliotropium ellipticum Exudate - Singh, Bharat; A. Sharma, Ram (Current Bioactive Compounds, 2016)
Heliotropium ellipticum is an herbaceous annual plant; and its resinous exudate is known for various types of therapeutic effects. The recent study was carried out to investigate the presence of flavonoids and their screening for anti-inflammatory and antimicrobial activities. The carrageenan and CFA-induced paw oedema models were adopted for the assessment of anti-inflammatory activity of dichloromethane fraction and isolated flavonoids. The disc diffusion and microdilution methods were used for the determination of antimicrobial activities. Five known flavonoids were isolated and characterized first time from resinous exudate of H. ellipticum. For the in vitro estimation of flavonoids, the callus cultures were established onto MS medium with supplementation of BAP (2.0 mg/l) and NAA (3.0 mg/l). On estimation, it was found that the flavonoids accumulated in higher concentration in intact plant while lower in callus cultures. Observed findings revealed that Chrysin demonstrated maximum inhibition (49.51%) at 4 h with 20 mg/kg dose in carrageenan-induced paw oedema models. The sakuranetin significantly reduced the CFA-induced arthritis (44.72%) with 10.0 mg/kg dose at day 6. The sakuranetin exhibited maximum antimicrobial activity against Bacillus subtilis (IZ=28.09±0.6 mm, MIC=10 μg/ml) and Candida albicans (IZ=22.06±0.6 mm, MIC=25 μg/ml) when antimicrobial activity was tested by disc diffusion and microdilution methods. The isolated flavonoids from this plant species demonstrated significant anti-inflammatory and antimicrobial activities. The isolated flavonoids from H. ellipticum showed the therapeutic efficacy in the treatment of inflammations and infections.
Keywords: carrageenan and CFA models